2020
DOI: 10.1186/s12978-020-00971-2
|View full text |Cite
|
Sign up to set email alerts
|

“They haven’t asked me. I haven’t told them either”: fertility plan discussions between women living with HIV and healthcare providers in western Ethiopia

Abstract: Background: Despite the importance of women living with HIV (WLHIV) engaging in fertility plan discussions with their healthcare providers (HCPs), little research exists. This study explored perceptions surrounding fertility plan discussions between WLHIV and their HCPs in western Ethiopia, from the perspectives of both women and providers. Methods: Thirty-one interviews (27 with WLHIV and 4 with HCPs) were conducted at four healthcare facilities in western Ethiopia in 2018. Data were transcribed verbatim and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…e study showed that most PLHAs and their partners had the same desire to have children [14]. Couples considered their own and their spouse's health and marital satisfaction when making reproductive decisions [15]. Preexposure prophylaxis, male circumcision, and ovulation monitoring could effectively reduce the spouse's risk of condom-free sex and HIV infection during pregnancy [16], and medically assisted reproductive technology could be used when it is necessary to reduce the risk of the partner and HIV infection.…”
Section: Related Workmentioning
confidence: 99%
“…e study showed that most PLHAs and their partners had the same desire to have children [14]. Couples considered their own and their spouse's health and marital satisfaction when making reproductive decisions [15]. Preexposure prophylaxis, male circumcision, and ovulation monitoring could effectively reduce the spouse's risk of condom-free sex and HIV infection during pregnancy [16], and medically assisted reproductive technology could be used when it is necessary to reduce the risk of the partner and HIV infection.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, in the context of HIV care, where individuals are seen repeatedly, there is an opportunity to develop such relationships. Discussions about family planning and fertility discussions could be layered onto such foundational relationships with providers within integrated HIV and SRH services ( 18 20 , 49 , 50 ). Additionally, provider support for women to select only the services that they wanted, including choosing not to take up certain options enables them to exercise agency.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns about drug-drug interactions and viral load being a determinant for eligibility to use contraceptives limited their perceived contraceptive options. Studies have shown that HIV providers have not always been confident in their knowledge to effectively provide quality family planning counseling for young WLHIV ( 18 , 32 34 , 49 , 58 ). Mixed messages from providers and subsequent incorrect comprehension may result in WLHIV discontinuing either ART or contraception.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations